The Influence of Brand Image, Brand Trust, Product Quality and Price on the Consumer’s Buying Decision in Nepalese Context - Sah, Pritti (Nepalese Journal of Economics, 2025)
This study examines influence of brand image, brand trust, product quality and price on the consumer’s buying decision in Nepalese context. Buying decision is the dependable variables. The independent variables are brand image, brand trust, product quality, price and brand loyalty. The study is based on primary data with 128 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and influence of brand image, brand trust, product quality and price on the consumer’s buying decision in Nepalese context. The study shows that brand image is positively correlated to buying decision. This means that better brand image leads to increase the consumer buying decision. Similarly, brand trust is positively related to buying decision indicating that higher the level of brand trust, higher would be the buying decision. Likewise, product quality has positive relationship with buying decision. It shows that higher the product quality, higher would be the buying decision. Similarly, price has negative relationship with buying decision. It reveals that lower the price, higher would be the buying decision. Brand loyalty has positive relationship with buying decision. It means higher brand loyalty, higher would be the buying decision.